Synthesis, Biological Evaluation, and Mode of Action of Pulsatilla Saponin D Derivatives as Promising Anticancer Agents - Fang, Yuanying; Hu, Daoyong; Li, Huilan; Hu, Jianguo; Liu, Yanhua; Li, Zhifeng; Xu, Guoliang; Chen, Lanying; Jin, Yi; Yang, Shilin; Yang, Zunhua (Frontiers in Pharmacology, 2019)
A series of ester and amide derivatives of triterpenoid saponin pulsatilla saponin D (PSD) were designed, synthesized and evaluated for their antiproliferative activity. Compounds 1 and 6 displayed 1.7~8.3 times more potent cytotoxicity (IC50 = 1.2-4.7 μM, 1.7-4.5 μM respectively) against five human tumor cell lines (SMMC-7721, MCF-7, NCI-H460, A549 and HCT-116) in vitro and lower acute toxicity to mice in vivo than PSD. Furthermore, compound 6 was observed to show potent tumor growth inhibition against mice H22 hepatocellular cells (49.8 % at 20 mg/kg) and induce cell cycle at G1 phase and apoptosis in HCT-116 cells.